Pointers in C A Hands on Approach - Toppo, Naveen. (Apress : Imprint: Apress, 2013)
Pointers in C provides a resource for professionals and advanced students needing in-depth but hands-on coverage of pointer basics and advanced features. The goal is to help programmers in wielding the full potential of pointers. In spite of its vast usage, understanding and proper usage of pointers remains a significant problem. This bookỚ"s aim is to first introduce the basic building blocks such as elaborate details about memory, the compilation process (parsing/preprocessing/assembler/object code generation), the runtime memory organization of an executable and virtual memory. These basic building blocks will help both beginners and advanced readers to grasp the notion of pointers very easily and clearly. The book is enriched with several illustrations, pictorial examples, and code from different contexts (Device driver code snippets, algorithm, and data structures code where pointers are used). Pointers in C contains several quick tips which will be useful for programmers for not just learning the pointer concept but also while using other features of the C language. Chapters in the book are intuitive, and there is a strict logical flow among them and each chapter forms a basis for the next chapter. This book contains every small aspect of pointer features in the C language in their entirety.